Dreaming Big in Post-War Greece: Neighborhood, Life Style, and Everyday Practices in the City of Thessaloniki - Zermpoulis, Miltiadis (transcript, 2023)
In post-war Greece, Western Allies, the country's conservative political elite and parts of the middle class share a dream of consolidating and maintaining the country's Western, bourgeois-liberal orientation. In 1947, with the civil war still raging in the country, the Greek government chooses the path of the capitalist countries and joins the American program for the reconstruction of war-torn Europe. Miltiadis Zermpoulis focuses on the impact and significance of the social and political changes brought about by the civil war, the dominance of conservatives in the political arena and the promotion of political surveillance and compliance technologies in the daily life of Greece's second largest city, Thessaloniki.